EVALUASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGATASI KEMISKINAN DI KAB.MAJALENGKA - Restin Nur Faidah; Amiruddin Setiawan (Jurnal Ilmu Administrasi CENDEKIA, 2023)
Poverty is a problem that hinders economic growth. Poverty is described as a lack of income to meet the basic necessities of life or the minimum necessities of life, namely clothing, food, shelter, education and health. To overcome poverty in Majalengka District,, one of them is the Family Hope Program (PKH). It is a conditional social assistance program aimed at families who have been designated as beneficiaries of assistance in the form of PKH to overcome poverty. One example of PKH's obligation is to ensure that every child in a family unit goes to school according to the elementary and high school levels through the provision of social assistance of up to 2 million. The Hope Assistance Program also provides many benefits for survival, for example assistance in the fields of health, education and most importantly to improve social welfare in the community. The research conducted in evaluating the application of this program uses descriptive qualitative research methods and also analysis. Which aims to evaluate the extent to which the Family Hope Program is implemented in Majalengka District, so that it can be seen that the Family Hope Program in Majalengka District, in its implementation has run quite optimally. Although there are still some residents who have obstacles in receiving the assistance or even unable to receive the assistance due to other reasons.PKeywords : PKH, Poverty,education, Health Kemiskinan merupakan salah satu masalah yang menghambat dari pertumbuhan ekonomi. Kemiskinan digambarkan sebagai kurangnya pendapatan untuk memenuhi kebutuhan hidup yang pokok atau kebutuhan hidup yang minimum yaitu sandang, pangan, papan, pendidikan dan kesehatan.Untuk mengatasi kemiskinan di Kabupaten Majalengka, salah satunya adalah Program Keluarga Harapan (PKH). Merupakan program bantuan sosial bersyarat yang ditujukan kepada keluarga yang telah ditetapkan sebagai penerima bantuan berupa PKH untuk mengatasi kemiskinan. Salah satu contoh kewajiban PKH adalah memastikan setiap anak dalam satu unit keluarga bersekolah sesuai jenjang SD dan SMA melalui pemberian bansos hingga 2 juta. Program Bantuan Harapan juga memberikan banyak manfaat untuk kelangsungan hidup, misalnya bantuan dalam bidang kesehatan, pendidikan dan yang terpenting untuk meningkatkan kesejahteraan sosial di masyarakat. Penelitian yang dilakukan dalam mengevaluasi penerapan program ini menggunakan metode penelitian deskriptif kualitatif dan juga analisis. Yang bertujuan untuk mengevaluasi sejauh mana Program Keluarga Harapan dilaksanakan di Kabupaten Majalengka, sehingga dapat diketahui bahwa Program Keluarga Harapan di Kabupaten Majalengka dalam pelaksanaannya sudah berjalan cukup optimal. Meski masih ada beberapa warga yang mengalami kendala dalam menerima bantuan atau bahkan tidak dapat menerima bantuan karena sebab lain.Kata Kunci : PKH,Kemiskinan, Pendidikan, Kesehatan